Program Pemberdayaan Mahasiswa Melalui Pelatihan Data Analysis Berbasis Artificial Intelligence Untuk Penulisan Karya Ilmiah - Heru Edi Kurniawan; Bambang Abdul Syukur (Yayasan Darussalam Bengkulu, 2026)
The rapid advancement of Artificial Intelligence (AI) has created new opportunities to enhance data analysis and academic writing in higher education. However, many students still face challenges in effectively utilizing AI due to limited AI literacy, data analysis skills, and understanding of ethical AI use in academic contexts. This community service program aimed to improve students’ competencies in AI-based data analysis, AI literacy, and ethical AI-assisted academic writing. The program was conducted on February 21, 2026, at Universitas Kusuma Husada Surakarta through a series of activities, including needs assessment, pre-test, instructional sessions, hands-on training using AI-based tools and Jamovi statistical software, post-test, and participant satisfaction evaluation. The results demonstrated significant improvements across all assessed domains. Scores for AI-based data analysis concepts increased from 50 to 85, AI literacy from 65 to 86, and ethical AI-assisted writing from 60 to 88. Participant satisfaction evaluation further revealed that more than 90% of participants expressed positive perceptions regarding the relevance of the training content, clarity of instruction, and overall program implementation. These findings indicate that the training effectively enhanced students’ digital literacy, data analysis competencies, and ethical awareness in utilizing AI to support research activities and academic writing